Heart health risk factors in Punjabi early teens - Elizabeth Mary John; Clarence James Samuel (Wolters Kluwer Medknow Publications, 2014)
Context: India is experiencing an epidemiological health transition characterized by rapid decline in nutritional and parasitic diseases (pre-transitional diseases) with an alarming rise in cardiovascular diseases, mainly coronary heart disease and stroke (post-transitional diseases). Many of these risk factors manifesting themselves as diseases in adults can be found during adolescence. Aims: To determine the prevalence of risk factors of heart disease among urban high-school students aged 13-15 yrs in Ludhiana city. Materials and Methods: This cross-sectional study included 330 high school-going early teens aged 13-15 years using a pretested questionnaire. Details regarding food habits, physical activity, and family history were collected along with anthropometric measures and blood pressure recordings. Statistical Analysis Used: Data was analysed using frequencies and proportion. Chi-square was the test of significance. Results: The prevalence of at least one risk factor in the population was 48.5%. Family history with prevalence of at least one coronary artery disease risk factor was of 27.4%, diabetic parents 12.2%, hypertension 17.6%, and heart disease was 1.8%. Physical inactivity as a risk factor showed an overall prevalence of 73%. Nearly 50% of the students consumed some junk food every day. Only 18.2% consume 3-5 servings of fruits per day, 11.2% do not take any fruits at all. Prevalence of overweight was 11.2% and 4.6% of them were obese. Hypertension was seen in 20.1% of subjects. Conclusions: The present generation of early teens are at high risk of future cardiovascular disease and schools and society need to address these issues urgently.